Ageing, Education, and Protein Intake Shape Nutritional Status in Indonesian Older Adults: A Population-Based Study - Akhmad Azmiardi; Muhamad Zakki Saefurrohim; Ratih Wirapuspita Wisnuwardani; Irfansyah Baharuddin Pakki (Masters Program in Public Health, Sebelas Maret University, 2026)
Background: The elderly population in Indonesia has increased rapidly, accompanied by health challenges such as malnutrition, which can lead to sarcopenia and physical weakness. Body weight is one indicator of nutritional status, which can be influenced by characteristics and nutrient intake, such as protein. This study aims to analyze the influence of age, gender, education and protein intake on nutritional status in the elderly in Indonesia. Subjects and Method: A cross-sectional study of the Indonesian Family Life Survey (IFLS-5) involved 2,908 individuals aged 60 and above. Sociodemographic variables (age, gender, education level, and marital status) were measured using a questionnaire, while protein intake was measured using a Food Frequency Questionnaire (FFQ). Bivariate data analysis was used to determine the relationship between age, gender, and protein intake and nutritional status and logistic regression analysis was used to evaluate factors influencing poor nutritional status. Results: Age ≥ 71 years (aOR= 2.14; 95%CI= 0.56 to 0.96; p<0.001), male (aOR=1.43; 95%CI= 0.16 to 0.55; p= 0.003) increase the risk of poor nutritional status, while education > Senior High School (aOR=0.22; 95%CI= -0.22 to -0.77; p<0.001), and high protein intake (aOR= 0.80; 95%CI= -0.42 to -0.02; p =0.033) are protective factors for poor nutritional status in the elderly. Conclusion: Age over 70 years and being male increases the risk of poor nutritional status, while high levels of education and protein intake reduce the risk of poor nutritional status in the elderly in Indonesia.